The Royal Court Theatre and the modern stage - Roberts, Philip 1942- (Cambridge Univ. Press, 1999)
An account of the Royal Court Theatre's history from 1956 to 1998, Philip Roberts's text is based upon archives in both public and private collections and a series of interviews with people prominent in the Court's life.
Keywords: Royal Court Theatre - History; Royal Court Theatre -- History; Royal Court Theatre -- London; Toneelgezelschappen; Toneelvoorstellingen; Geschichte